Predictive Genetic Testing of a Bone Marrow Recipient–Ethical Issues Involving Unexpected Results, Gender Issues, Test Accuracy, and Implications for the Donor. Issue 1 (30th August 2013) - Sexton, A.; Rawlings, L.; Jenkins, M.; Winship, I.
Abstract: We present a case where an apparently straightforward Lynch syndrome predictive genetic test of DNA from a blood sample from a woman yielded an unexpected result of X/Y chromosome imbalance. Furthermore, it demonstrates the complexities of genetic testing in people who have had bone marrow transplants. This highlights the potential for multiple ethical and counselling challenges, including the inadvertent testing of the donor. Good communication between clinics and laboratories is essential to overcome such challenges and to minimise the provision of false results.